RETRACTED: The efficiency of growing turkey for meat - Smolentsev Sergey; Ivanov Ivan; Krysenko Yuriy; Fedorova Natalya; Samatova Albina; Mishina Nailya; Kamalova Zilya; Samsonov Andrey; Markova Evgenia; Pavlenko Igor (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001